Strategies for overcoming therapeutic inertia in type 2 diabetes: A systematic review and meta‐analysis. Issue 9 (27th June 2021) - Powell, Rhea E.; Zaccardi, Francesco; Beebe, Christine; Chen, Xin Mei; Crawford, Alyssa; Cuddeback, John; Gabbay, Robert A.; Kissela, Lauren; Litchman, Michelle L.; Mehta, Rajesh; Meneghini, Luigi; Pantalone, Kevin M.; et al.
Abstract: Aims: To systematically investigate the effect of interventions to overcome therapeutic inertia on glycaemic control in individuals with type 2 diabetes. Materials and Methods: We electronically searched for randomized controlled trials or quasi‐experimental studies published between January 1, 2004 and December 31, 2019 evaluating the effect of interventions on glycated haemoglobin (HbA1c) control. Characteristics of included studies and HbA1c difference between intervention and control arms (main outcome) were extracted. Interventions were grouped as: care management and patient education; nurse or certified diabetes educator (CDE); pharmacist; or physician‐based. Results: Thirty‐six studies including 22 243 individuals were combined in nonlinear random‐effects meta‐regressions; the median (range) duration of intervention was 1 year (0.9 to 36 months). Compared to the control arm, HbA1c reduction ranged from: −17.7 mmol/mol (−1.62%) to −4.4 mmol/mol (−0.40%) for nurse‐ or CDE‐based interventions; −13.1 mmol/mol (−1.20%) to 3.3 mmol/mol (0.30%) for care management and patient education interventions; −9.8 mmol/mol (−0.90%) to −6.6 mmol/mol (−0.60%) for pharmacist‐based interventions; and −4.4 mmol/mol (−0.40%) to 2.8 mmol/mol (0.26%) for physician‐based interventions. Across the included studies, a reduction in HbA1c was observed only during the first year (6 months: −4.2 mmol/mol, 95% confidence interval [CI] −6.2, −2.2 [−0.38%, 95% CI −0.56, −0.20]; 1 year: −1.6 mmol/mol, 95% CI −3.3, 0.1 [−0.15%, 95% CI −0.30, 0.01]) and in individuals with preintervention HbA1c >75 mmol/mol (9%). Conclusions: The most effective approaches to mitigating therapeutic inertia and improving HbA1c were those that empower nonphysician providers such as pharmacists, nurses and diabetes educators to initiate and intensify treatment independently, supported by appropriate guidelines.